Psychiatric comorbidity in patients with spasmodic dysphonia: a controlled study. Issue 12 (5th July 2007) - Gündel, H; Busch, R; Ceballos-Baumann, A; Seifert, E
Abstract : Objectives: To study the prevalence of psychiatric comorbidity assessed by a structured clinical interview in patients with spasmodic dysphonia (SD) compared with patients suffering from vocal fold paralysis (VFP). Methods: In 48 patients with SD and 27 patients with VFP, overall psychiatric comorbidity was studied prospectively using the Structured Clinical Interview for DSM-IV Axis I disorders. Physical disability and psychometric variables were assessed with standardised self-rating questionnaires. Results: 41.7% of SD subjects and 19.5% of the control group met DSM-IV clinical criteria for current psychiatric comorbidity (p<0.05). Significant predictors of psychiatric comorbidity in SD were severity of voice impairment and subjective assessment of "satisfaction with health". As a limitation, the severity of voice impairment in patients with SD was nearly twice as high, and their illness had lasted nearly twice as long. Conclusions: We found a high prevalence of psychiatric comorbidity in patients with SD. The significant correlation between current psychiatric comorbidity and the extent of voice pathology may point to an especially strong interaction between somatic and psychiatric complaints in SD.